Polarimetric observations of the Galilean satellites near opposition in 2011 - Zaitsev, S.V.; Kiselev, N.N.; Rosenbush, V.K.; Velichko, F.P.; Kolesnikov, S.V.; Antonyuk, K.A.; Psarev, V.N. (Advances in Astronomy and Space Physics, 2012)
We present results of the new polarimetric observations of the Galilean satellites Io, Ganymede, Europe, and Callisto carried out on October 21 - November 1, 2011. We used 1.25m telescope equipped with the UBVRI double image chopping photoelectric polarimeter, 2.6m Shain telescope equipped with a one-channel photoelectric photometer-polarimeter, 1m RCC telescope equipped with a one-channel photoelectric photometer-polarimeter (Crimean Astrophysical Observatory, Ukraine), and 0.7m telescope equipped with a one-channel photoelectric photometer-polarimeter (Chuguev Observational Station of Astronomical Institute of Karazin Kharkiv National University, Ukraine). The measurements were performed at phase angles ranging from 0.34° to 2.12°. Our new observations fully confirmed the presence of the polarization opposition effect for high-albedo satellites Io, Europa, and Ganymede at phase angles less than 2° . Within the accuracy of the measurements we did not detect the polarization opposition effect for moderate-albedo satellite Callisto.